2019
DOI: 10.1002/cctc.201901996
|View full text |Cite
|
Sign up to set email alerts
|

CoOx@Co Nanoparticle‐based Catalyst for Efficient Selective Transfer Hydrogenation of α,β‐Unsaturated Aldehydes

Abstract: Currently, developing simple and effective catalysts for selective hydrogenation of α,β‐unsaturated aldehydes to unsaturated alcohols is challenging. Herein, an efficient CoOx‐shell/Co‐core structured nanoparticle catalyst is synthesized by a facile ultrasonic‐assisted carbothermal reduction method. The resultant catalyst exhibits outstanding catalytic performance toward the selective transfer hydrogenation of a wide spectrum of α,β‐unsaturated aldehydes into corresponding unsaturated alcohols with over 90 % s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Interestingly, beyond 80 8C, the COL selectivity decreased rapidly to 24.6 %, accompanying by the rapidly increased HCOL selectivity from 5.5 to 73.0 %. These indicate that the rapidly decreased COL selectivity at higher temperatures is due to the occurrence of hydrogenation on both C = O and C = C. [31] The effect of reaction time was then evaluated under 2 MPa H 2 pressure and 80 8C. As revealed in Figure 2 b, an increase in the reaction time from 0.5 to 2 h leads to a rapid increase in CAL conversion from 44.5 to 95.1 % and further increase in the reaction time results in a neglectable increase in CAL conversion.…”
Section: Angewandte Chemiementioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, beyond 80 8C, the COL selectivity decreased rapidly to 24.6 %, accompanying by the rapidly increased HCOL selectivity from 5.5 to 73.0 %. These indicate that the rapidly decreased COL selectivity at higher temperatures is due to the occurrence of hydrogenation on both C = O and C = C. [31] The effect of reaction time was then evaluated under 2 MPa H 2 pressure and 80 8C. As revealed in Figure 2 b, an increase in the reaction time from 0.5 to 2 h leads to a rapid increase in CAL conversion from 44.5 to 95.1 % and further increase in the reaction time results in a neglectable increase in CAL conversion.…”
Section: Angewandte Chemiementioning
confidence: 89%
“…Interestingly, beyond 80 °C, the COL selectivity decreased rapidly to 24.6 %, accompanying by the rapidly increased HCOL selectivity from 5.5 to 73.0 %. These indicate that the rapidly decreased COL selectivity at higher temperatures is due to the occurrence of hydrogenation on both C=O and C=C [31] . The effect of reaction time was then evaluated under 2 MPa H 2 pressure and 80 °C.…”
Section: Figurementioning
confidence: 98%
“…However, at temperatures beyond 80 °C, the CMA conversion and the CMO selectivity decreased and the HCMO selectivity increased significantly, which resulted from the excessive hydrogenation at high temperature. 37 As revealed in Fig. 3c and Table S2, † the CMA conversion and CMO selectivity rate increased first and then decreased with the prolongation of the reaction time from 0.5 to 2.5 h. When the reaction time was 2 h, the CMA conversion and CMO selectivity rate reached as high as 94.1% and 95.1%, respectively.…”
Section: Dalton Transactions Papermentioning
confidence: 73%
“…This indicated that the higher the polarity of the solvent, the higher the conversion of CAL, which was in good agreement with recent studies. 31,42 Additionally, the stability of a heterogeneous catalyst was an important factor for its practical application. Hence, a recycling test (total 4 cycles) was carried out, and Pt 1 /Fe 2 O 3 showed excellent stability in conversion (86.9%) and selectivity to COL (80.5%, Fig.…”
Section: Dalton Transactions Communicationmentioning
confidence: 99%